Analysis of postural stability in response to external perturbation intensity in dancers and non-dancers - Park, D. W.; Koh, K.; Lee, S. R.; Park, Y. S.; Shim, J. K. (Korean Journal of Sport Biomechanics, 2016)
Objective: The goal of this study was to systematically investigate the postural stability of dancers by providing unexpected perturbations. Method: Six female dancers and college students participated in this study. Unpredictable wait-pull balance perturbations in the anterior direction were provided to the participants during standing. Three different perturbation intensities (low, moderate, and high intensity) were used by increasing perturbation forces. Spatial and temporal stability of postural control were measured by using margin of stability (MoS) and time to contact (TtC), respectively. Results: Both MoS and TtC at moderate intensity were significantly greater in the dancer group than in the control group, but no significant differences were found at low and high intensities between the groups. Conclusion: The present study showed spatial and temporal stability of dynamic postural control in dancers. We found that the dancers were more spatially and temporally stable than the ordinary participants in response to unexpected external perturbation when the perturbation intensity was moderate at two extreme intensity levels (low and high).